The Changing Face of the Channel Islands Occupation - Smith, Hazel R. Knowles. author. aut Link
XXIII, 288 p.
Keywords: This independent study has already attracted controversy. Containing much fresh evidence, it vividly portrays the Islanders' day-to-day Occupation experiences, whilst exploring - and often refuting - what are today becoming received ideas of a mostly 'shameful' wartime past.